Performance of Pretreatment Materials on Hospital Wastewater Before Microfiltration Membrane Filtration Process (Applied Research in Science and Technology, 2022)
An alternative method of treating hospital wastewater can use a microfiltration membrane, where the results showed that the disposal of oily wastewater reached 82.5%, BOD 90%, COD 85%, and total Coli up to 70%. In addition, it can remove particles from wastewater from 0.04 to 100 microns in size. The problem with using microfiltration membranes is the rapid occurrence of fouling/saturation on the surface of the microfiltration membrane, causing the wastewater treatment operation time to be short. The length of this treatment causes the problem of less amount of wastewater being treated and another problem, namely faster membrane replacement. This study aims to determine the performance of pretreatment of microfiltration membranes made of alum, silica sand, and activated carbon for parameters pH, BOD, COD, TSS, Ammonia, Fatty Oil, and Total Coliform. The results of the study were as follows: 1) the average quality of hospital wastewater was temperature 28.8°C, pH 7, BOD 79 mg/l, COD 167.05 mg/l, Total Suspended Solid 68 mg/l, Ammonia 4 mg/l, Phosphate 0.745 mg/l, Fatty Oil 1.64 mg/l, Coliform 2.200 MPN/100 ml. 2) Comparison analysis of the most effective materials on the parameters, for BOD Silica Sand 78.24%, COD 56.25% Silica Sand, Total Suspended Solids 83.42% Activated Carbon, Ammonia Silica Sand 56.49%, Phosphate 80.43 % Activated Carbon, Fat Oil is 80.43% Alum, Coliform is Microfiltration Membrane 40.91%.